Investigations of the dual contractile/relaxant properties showed by antioquine in rat aorta. - Ivorra, M. D. (Nature Publishing Group, 1993)
1. In the present study we assessed the activity of antioquine, a bisbenzyltetrahydroisoquinoline alkaloid isolated from Pseudoxandra sclerocarpa, by examining its effects on the contractile activity of rat isolated aorta, specific binding of [3H]-(+)-cis-diltiazem, [3H]-nitrendipine and [3H]-prazosin to cerebral cortical membranes and the different molecular forms of cyclic nucleotide phosphodiesterases (PDE) isolated from bovine aorta. 2. Contractions in rat aorta induced by high concentrations of KCl (80 mM) and noradrenaline (1 microM) were inhibited by antioquine in a concentration-dependent manner (0.1 microM- 300 microM). The alkaloid appeared more potent against KCl-induced contractions. This inhibitory effect was observed at both 37 degrees C and 25 degrees C. 3. Paradoxically, at the highest concentration tested (300 microM) antioquine induced a contractile response of similar magnitude in the presence and absence of extracellular calcium, at 37 degrees C. This activity was greatly attenuated at 25 degrees C. Antioquine-induced contractions were not inhibited by prazosin (0.1 microM), nifedipine (1 microM) or diltiazem (100 microM). On the contrary, prazosin and nifedipine slightly increased the contractions in the presence of extracellular calcium. Papaverine (100 microM) partially inhibited the contractile response to antioquine both in the presence and absence of extracellular calcium. 4. At 25 degrees C, in Ca(2+)-free solution, antioquine (300 microM) did not modify the contractile response (phasic and tonic) evoked by noradrenaline, but increased the phasic contraction induced by caffeine. At 37 degrees C, the contraction elicited by antioquine made it impossible to observe the noradrenaline-induced one.(ABSTRACT TRUNCATED AT 250 WORDS)